Sexual dimorphism and phenotypic plasticity in the antennal lobe of a stingless bee, Melipona scutellaris - Roselino, Ana Carolina [UNESP]; Hrncir, Michael; Landim, Carminda da Cruz [UNESP]; Giurfa, Martin; Sandoz, Jean-Christophe (Wiley-Blackwell, 2015)
Among social insects, the stingless bees (Apidae, Meliponini), a mainly tropical group of highly eusocial bees, present an intriguing variety of well-described olfactory-dependent behaviors showing both caste- and sex-specific adaptations. By contrast, little is known about the neural structures underlying such behavioral richness or the olfactory detection and processing abilities of this insect group. This study therefore aimed to provide the first detailed description and comparison of the brains and primary olfactory centers, the antennal lobes, of the different members of a colony of the stingless bee Melipona scutellaris. Global neutral red staining, confocal laser scanning microscopy, and 3D reconstructions were used to compare the brain structures of males, workers, and virgin queens with a special emphasis on the antennal lobe. We found significant differences between both sexes and castes with regard to the relative volumes of olfactory and visual neuropils in the brain and also in the number and volume of the olfactory glomeruli. In addition, we identified one (workers, queens) and three or four (males) macroglomeruli in the antennal lobe. In both sexes and all castes, the largest glomerulus (G1) was located at a similar position relative to four identified landmark glomeruli, close to the entrance of the antennal nerve. This similarity in position suggests that G1s of workers, virgin queens, and males of M. scutellaris may correspond to the same glomerular entity, possibly tuned to queen-emitted volatiles since all colony members need this information. J. Comp. Neurol. 523:1461-1473, 2015. (c) 2015 Wiley Periodicals, Inc.
Keywords: stingless bees; worker; queen; male; three-dimensional reconstruction; macroglomerulus; behavior; RRID nif-0000-00262